2007
DOI: 10.5650/jos.56.623
|View full text |Cite
|
Sign up to set email alerts
|

Development of Mineral Oil Free Offset Printing Ink Using Vegetable Oil Esters

Abstract: Until the middle of this century, fats and oils are the major raw material source for paints, coating and lubricating applications. These markets are completely taken over by petroleum based stocks due to their abundance and versatility. However, recent public awareness to use environmentally acceptable products that minimize pollution, are compatible to human health and readily biodegradable created opportunities for vegetable oils for application in paints and printing inks. The formulation of vegetable oil … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(29 citation statements)
references
References 2 publications
0
27
0
2
Order By: Relevance
“…To ensure a high quality of paper and board for recycling, the chemicals of concern can be substituted by alternatives of reduced hazard. For example, vegetable oils can be used in place of mineral oils in printing process (Roy et al, 2007), while variety of phenol-based and phenol-free alternatives to BPA can be used in thermal paper (US EPA, 2014). Alternatively, fractions with high levels of problematic chemicals could potentially be removed from the source-segregated flows sent to recycling.…”
Section: Implications Of the Resultsmentioning
confidence: 99%
“…To ensure a high quality of paper and board for recycling, the chemicals of concern can be substituted by alternatives of reduced hazard. For example, vegetable oils can be used in place of mineral oils in printing process (Roy et al, 2007), while variety of phenol-based and phenol-free alternatives to BPA can be used in thermal paper (US EPA, 2014). Alternatively, fractions with high levels of problematic chemicals could potentially be removed from the source-segregated flows sent to recycling.…”
Section: Implications Of the Resultsmentioning
confidence: 99%
“…Among the vegetable esters, FAME shows lower rub resistance due to the low surface smoothness of ink film than FABE, and FAEE gives better rub resistance due to better printing density even if the kinematic viscosity of the solvent is lower. In a similar study 6 , it was found that vegetable esters of good compatibility gave better printing density, gloss, and ink transfer than hydrocarbon solvent. Though the esters give similar printing properties of density, gloss and rub resistance, the smallest change of ink transfer weight upon multiple number of printing obtained from FABE improves the stability of ink quality the most.…”
Section: Fatty Acid Estersmentioning
confidence: 93%
“…7 Since the majority of inks employed in digital ink-jet printing are based on organic solvents and contain volatile organic compounds (VOCs) to ensure their dispersion stability and printability, the development of ecofriendly and functional ceramic inks to replace VOC-containing organic solvent-based ink-jet printing inks is required. 8,9 As such, the physical properties of existing ceramic inks must be satised to ensure successful ink-jet printing for the decoration of ceramic tiles. [10][11][12][13] In this context, the ceramic pigments present in ceramic ink must be thermally stable to ensure that the desired color is maintained at sintering temperatures >1000 C. In addition, the pigment particles should show an appropriate particle size distribution and a high dispersion stability to prevent nozzle clogging of the inkjet printer head.…”
Section: Introductionmentioning
confidence: 99%